Georg von Charasoff's theory of value, capital and prices of production - Thomas Huth (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
The present paper on the now partly well known Russian mathematician and amateur economist v. Charasoff was originally written in 1987 together with H. Duffner three years after Charasoff's remarkable contribution of 1910 Das System des Marxismus (The system of Marxism) had been rediscovered by the Italian economists Gilibert and Egidi. It was then the second mathematical formulation of Charasoff's contribution on prominent but partly still unresolved topics in Marxian economics. However, though our paper circulated as mimeo it had not been published in a regular journal of economics. Meanwhile, several contributions on Charasoff appeared by such authors as Egidi, Gilibert, Kurz and Salvadori, Stamatis and Mori. But none of them seems to deal with Charasoff's economics in an exhaustive manner. Therefore and nevertheless, the paper may be still of some interest to the, nowadays regrettably rather narrow, audience of economists specialized in linear models of production, Marxian economic theory and Neoricardianism.
Keywords: B14; B51; C67; D24; 330; Marxian economics; labor theory of value; transformation problem; prices of production